A Study on Incidence, Pattern of Clinical Features, Laboratory Abnormalities and Outcome of Neonatal Polycythaemia in a Tertiary Care Hospital, Odisha, India - Swarupa Panda; Simanta Das; Deepak Behera; Sanaga Meghna; Suchismita Mahapatra; Nibedita Pradhan (JCDR Research and Publications Pvt. Ltd., 2023)
Introduction: Neonatal polycythaemia is a commonly encountered morbidity and mortality among neonates admitted to neonatal care units and sick newborn care units. Most affected infants have no clinical symptoms and signs, but neonates may present with lethargy, poor feeding, plethora, cyanosis and jaundice within 12-72 hrs. Aim: To find out the incidence and clinical manifestations of neonatal polycythaemia along with detection of disease by laboratory abnormalities. Materials and Methods: This was a hospital-based, prospective, observational study conducted in the Neonatal Care Unit of Sriram Chandra Bhanja Medical College, Eastern Odisha, India, in 1760 neonates, from October 2018 to September 2020. All neonates admitted through Outdoor and Emergency were included in this study irrespective of gestation, birth weight, maturity and mode of delivery with haematocrit >65% at 12 hours of life. These polycythaemic babies were further categorised on the basis of maturity, gestational age, birth weight, gender and the clinical features, laboratory abnormalities were noted, Partial Exchange Transfusion (PET) when required was done through central route, the umbilical venous catheter was used for withdrawing blood while same amount of normal saline was replaced through a peripheral vein, and in asymptomatic cases additional fluid of 20 mL/kg was added to the daily fluid requirements either through enteral or parenteral route and outcomes were noted. Short-term outcome at 48 hours was measured by decreasing haematocrit with improvement of signs and symptoms. Chi-square test was employed to analyse the collected data using Statistical Package for the Social Sciences (SPSS) software version 20.0. The p-value <0.05 was considered statistically significant. Results: Out of 1760 newborns enrolled, (n=75) were polycythaemic. The Incidence of polycythaemia was 4.26%), which was significantly higher among Small for Gestational Age (SGA) compared to Large for Gestational Age (LGA) neonates (p-value=0.0214). Clinical features in decreasing order were lethargy (66.6%), poor feeding (66.6%), Plethora (53.3%), cyanosis (40%) and jaundice (33.3%). Main laboratory abnormalities were hypoglycaemia (36%), hyperbilirubinaemia (28%), thrombocytopenia (22.66%) and hypocalcaemia (13.3%). Out of 75 polycythemic neonates, n=17 (22.67%) underwent PET and rest 58 (77.33%) neonates were treated with extra fluid of 20 mL/kg/day. Conclusion: Study showed that lethargy and poor feeding were the main presentation and hypoglycaemia as the major laboratory abnormality. The incidence of polycythaemia was high among SGA neonates and the response to partial exchange transfusion as well as extra fluid was good which was characterised by decreasing haematocrit values with improvement of signs and symptoms.